2006
DOI: 10.1073/pnas.0602320103
|View full text |Cite
|
Sign up to set email alerts
|

The peptide-catalyzed stereospecific synthesis of tetroses: A possible model for prebiotic molecular evolution

Abstract: Using a water-based prebiotic model of sugar synthesis involving glycolaldehyde self-condensation, we demonstrate that homochiral L-dipeptide catalysts lead to the stereospecific syntheses of tetroses. The asymmetric effect is largest for erythrose, which may reach a D-enantiomeric excess of >80% with L-Val-L-Val catalyst. Based on results obtained with various peptides, we propose a possible catalytic-reaction intermediate, consisting of an imidazolidinone ring formed between the two nitrogen atoms of the pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 24 publications
3
72
0
Order By: Relevance
“…Our signalling model suggests that there existed a reproductive benefit to encoding even short strings of polypeptides, whereas the usage of each codon was still nascent. Even short proteins might have provided structural support to protocells or had catalytic activity with specificity, as has been observed in some dipeptides [22]. Incorporating amino acids into an elongating polypeptide using a nucleic acid template may also have prevented those amino acids from doing harm to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our signalling model suggests that there existed a reproductive benefit to encoding even short strings of polypeptides, whereas the usage of each codon was still nascent. Even short proteins might have provided structural support to protocells or had catalytic activity with specificity, as has been observed in some dipeptides [22]. Incorporating amino acids into an elongating polypeptide using a nucleic acid template may also have prevented those amino acids from doing harm to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Polypeptides are known to catalyze the oligomerization of nucleotides, which can lead to the development of genetic material (Barbier et al, 1993); additionally, polypeptides help certain RNA-related molecules to function efficiently (Shimizu, 1995;Kochavi et al, 1997;van der Gulik et al, 2009). Moreover, some chiral dipeptides catalyze the stereoselective synthesis of biomolecules (Weber and Pizzarello, 2006;Pizzarello and Weber, 2010) and may be responsible for the homochirality of biomolecules that is a distinctive feature of terrestrial life.…”
Section: Introductionmentioning
confidence: 99%
“…Pizzarello and Weber, however, have recently demonstrated that the non-racemic amino acids in meteorites such as isovaline can transfer their chiral information to other prebiotic building blocks, for example in the formation of tetrose sugars from glycolaldehyde by aldol addition [71]. Similar stereoselectively catalytical properties could also be observed for asymmetric amino acid dipeptides in the formation of pentose and tetrose sugars [89,90]. In this context it is also interesting to note that α-methyl-amino acids, such as isovaline, are known as "long-term carriers" of chiral information because of their relative stability to chemical racemization [91], whereas sugars and other amino acids missing substituents at the "weakly" acidic stereogenic C2 position could have lost any enantiomeric excess, if it existed, via racemization.…”
Section: Enantiomeric Enrichment In Meteoritic Amino Acidsmentioning
confidence: 57%